2004
DOI: 10.1248/cpb.52.1367
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Enantiopure Norbornane Ligands Bearing Both (2S,3S)-Bis(phosphinomethyl) and 7-syn-Oxygen Functional Groups and an Application to Rhodium-Catalyzed Asymmetric Hydrogenation

Abstract: Development of efficient methods for the practical enantioselective synthesis of chiral compounds has been one of the most important subjects in synthetic organic chemistry. 1)Many kinds of enantioselective syntheses employing various catalysts such as metal complexes coordinated with chiral ligands have been reported for more than three decades, [1][2][3][4][5][6] and several optically pure compounds prepared by enantioselective synthesis with the chiral catalysts are now commercially available (e.g. opticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Table 3. According to the procedure reported previously, 32,33) the hydrogenation product 16 was isolated and the enantiomeric excess was determined by HPLC after conversion to its N-benzoyl derivative. All the results are summarized in Table 3.…”
mentioning
confidence: 99%
“…Table 3. According to the procedure reported previously, 32,33) the hydrogenation product 16 was isolated and the enantiomeric excess was determined by HPLC after conversion to its N-benzoyl derivative. All the results are summarized in Table 3.…”
mentioning
confidence: 99%
“…[11] It was shown that upon treatment of norbornenones with bromine the corresponding bromolactones were obtained in good yields. When exposed to silver(I) salts, these structures undergo a rearrangement via a non-classical cation to give, upon treatment with basic methanol, norbornenyl diester derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to NAPHOS, Ph-o-NAPHOS has a more rigid structure and provides higher enantioselectivities. The chiral norbornane diphosphine ligands, 15 and 16, were reported by Morimoto, and applied in Rh-catalyzed enantioselective hydrogenation [84]. Zhou reported a family of chiral spirodiphosphine ligands such as SDP, containing 1,1'-spirobi-indane as a new scaffold, which are effective for the hydrogenation of simple ketones (Fig.…”
Section: Other Bisphosphine Ligandsmentioning
confidence: 99%